Analisis Kinerja Reksadana Saham dan Reksadana Indeks dalam Penilaian Tingkat Efisiensi Pasar Modal di Indonesia - Aziqoh, Ainani Nur (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2021)
Mutual funds are designed to raise investment funds. The objectives of this study are: to determine the performance of mutual funds on the LQ-45 index is higher than the performance of equity funds in the Indonesian capital market and to measure the level of efficiency in the capital market using CAPM modeling and using Net Active Value (NAV) data per year for the 2015 period. -2019. To determine whether a mutual fund is good or bad, it is not measured by how much the return has been generated or by how big or small the risk of fluctuation is, but this is seen from how much the mutual fund performs with its reference index. If the performance of index mutual funds is better or the performance of stock mutual funds is lower overall, the capital market can be said to be efficient. The results of this study indicate that the performance of the LQ-45 index mutual funds is smaller than the performance of the more superior stock mutual funds above. So it can be concluded that the Indonesian capital market is an inefficient Indonesian capital market.